The impact of advertising value of in-game pop-up ads in online gaming on gamersâ inspiration: An empirical investigation - Abbasi, A.Z. (Elsevier Ltd, 2021)
In online gaming, pop-up ads are effective advertising strategies with a high conversion rate. Businesses are actively using pop-up ads in online games for advertising. However, research into the advertising value of pop-up ads and its effect on gamersâ inspiration states remains scarce. This study aims to deepen our understanding of the value of in-game pop-up ads by applying the Ducoffe advertising value model. Specifically, we investigated the factors that determine the advertising value of gamersâ inspired-by state and its resultant impact on the inspired-to state. Based on survey data of 321 online game players, the proposed conceptual model was tested using the Partial Least Squares (PLS) method. This study shows that incentives, entertainment, credibility, personalization, and irritation significantly impact the advertising value associated with online game pop-up ads. Additionally, this study empirically proves that the advertising value of in-game pop-up ads positively derives the inspired-by state, which in turn determines gamersâ inspired-to state. Beyond theoretical significance, this study offers several practical implications for advertising platforms and advertisers who want to attract gamers using pop-up ads. Â© 2021 Elsevier Ltd